The Role of Brand Image in Mediating the Effect of Promotional Appeal on Customer Loyalty - Jessica Sheva Angeline; Ni Made Rastini (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the mediating role of brand image in the effect of promotional appeal on customer loyalty, specifically in the context of Jiniso fashion products. The research was conducted in Denpasar City using a non-probability sampling method with a purposive sampling technique. A total of 100 respondents were selected based on specific criteria relevant to the study objectives. The data were analyzed using inferential statistical techniques, including path analysis, the Sobel test, and the Variance Accounted For (VAF) test to determine the direct and indirect effects between variables. The results of the study show that promotional appeal has a positive and significant effect on customer loyalty, indicating that attractive and persuasive promotional strategies are capable of increasing consumer commitment to the brand. Furthermore, promotional appeal has a positive and significant effect on brand image, meaning that well-designed promotional messages help build a favorable perception of the brand among customers. The findings also reveal that brand image has a positive and significant effect on customer loyalty, demonstrating that a strong brand image enhances customer retention and repeated purchases. Importantly, the analysis indicates that brand image partially mediates the relationship between promotional appeal and customer loyalty. This suggests that while promotional appeal directly influences loyalty, it also indirectly enhances loyalty through the improvement of brand image. These findings provide practical implications for marketers and brand managers, emphasizing the importance of developing integrated marketing strategies that combine promotional efforts with brand-building activities to strengthen customer loyalty in the competitive fashion industry. Future research could examine other mediating factors or expand the study to other sectors to increase external validity.